Similar mortality risk in incident cognitive impairment and dementia: Evidence from the ASPirin in Reducing Events in the Elderly (ASPREE) trial. Issue 12 (17th September 2021) - Lin, Xiaoping; Banaszak‐Holl, Jane; Xie, Jing; Ward, Stephanie A.; Brodaty, Henry; Storey, Elsdon; Shah, Raj C.; Murray, Anne; Ryan, Joanne; Orchard, Suzanne G.; Fitzgerald, Sharyn M.; McNeil, John J.
Abstract: Background: This study examined the risk of mortality in older adults with newly detected cognitive impairment or dementia. Methods: Data from the Australian cohort of the ASPirin in Reducing Events in the Elderly (ASPREE) trial were examined. The ASPREE clinical trial compared daily low‐dose aspirin to a placebo and involved 16, 703 individuals aged 70 years and over, who were without major cognitive impairment, physical disability, or cardiovascular disease at recruitment. During the trial, evidence of cognitive impairment, based on cognitive testing and medical record information, triggered dementia adjudication of participants using DSM‐IV criteria. Cox proportional hazard models were used to compare mortality rates across the dementia, trigger‐only, and no‐trigger groups. Results: Over a median 4.7‐year follow‐up period, 806 participants triggered dementia adjudication, with 485 (60.2%) judged to have dementia. Following recruitment, mortality risks were 32.9, 33.6, and 10.8 events per 1000 person‐years in the dementia, trigger‐no‐dementia, and no‐trigger groups, respectively. In the fully adjusted model, mortality risks remained higher in the dementia and trigger‐no‐dementia groups, with hazard ratios of 1.7 (95% CI: 1.3–2.1) and 1.9 (95% CI: 1.5–2.6), respectively. There was no discernible difference between the dementia and trigger‐no‐dementia groups in mortality rates following recruitment, or following a dementia trigger. These two groups were more likely to die from sepsis, respiratory disease, and dementia, but less likely to die from cancer than the no‐trigger group, χ 2  = 161.5, p  < 0.001. Conclusion: ASPREE participants who triggered for a dementia evaluation experienced a substantially higher mortality rate than those who remained cognitively intact. The increase was indistinguishable among persons who met DSM‐IV criteria for dementia vs. those who triggered for a dementia evaluation but failed to meet DSM‐IV criteria. Future work should investigate whether earlier detection of cognitive decline can be used to identify and prevent early mortality.